Musalogue (a catalogue of Musa germplasm): Diversity in the genus Musa - Daniells, J.; Jenny, C.; Karamura, D.; Tomekpe, Kodjo; International Network for the Improvement of Banana and Plantain (2001)
INIBAP has just published the second edition of Musalogue - a catalogue of Musa diversity. This publication provides descriptions and photographs of species and varieties covering most of the diversity in the genus Musa. Each entry in the catalogue is represented by a photograph and a morpho-taxonomic description of the plant in the field. The publication is based on information provided to INIBAP through the Musa Germplasm Information System (MGIS) by germplasm curators from Guadeloupe, Cameroon, Australia and Uganda.